In Silico Analysis of Cellulose Synthase Gene (NcCesA1) in Developing Xylem Tissues of Neolamarckia Cadamba - Tiong Shing Y, Yiing; Ho Wei, Seng; Pang Shek, Ling; Ismail, Jusoh (Science Publications, 2015)
This study reported the isolation and in silico characterization of full-length cellulose synthase (CesA) cDNA from Neolamarckia cadamba, an important tropical plantation tree species. CesA is a member of processive glycosyltransferases that involved in cellulose biosynthesis of plants. CesA acts as a central catalyst in the generation of plant cell wall biomass or cellulose. It also plays an important role in regulating wood formation. The hypothetical full-length CesA cDNA (NcCesA1; JX134621) was assembled by contig mapping approach using the CesA cDNA sequences from NcdbEST and the amplified 5â-and 3â-RACE PCR sequences. The NcCesA1 cDNA has a length of 3,472 bp with 3,126 bp open reading frame encoding a 1,042 amino acid sequence. The predicted NcCesA1 protein contained N-terminal cysteine rich zinc binding domain, 7 putative Transmembrane Helices (TMH), 4 U-motifs that contain a signature D, D, D, QxxRW motif, an alternating Conserved Region (CR-P) and 2 Hypervariable Regions (HVR). These entire shared domain structures suggest the functional role of NcCesA1 is involved in glycosyltransferation of the secondary cell wall cellulose biosynthesis of N. cadamba. Sequence comparison also revealed the high similarity (90%) among NcCesA1 and PtrCesA2 of Populus tremuloides. This further implies the involvement of NcCesA1 that catalyzes the cellulose biosynthesis of secondary cell wall rather than primary cell wall. This full-length NcCesA1 cDNA can serve as good candidate gene in association genetics study which leads to Gene-Assisted Selection (GAS) in the N. cadamba tree breeding programme. Furthermore, the isolation of new CesA genes from tropical tree genomes is essential for enhancing knowledge of cellulose biosynthesis in trees that has many fundamental and commercial implications.